1982
DOI: 10.1161/01.hyp.4.3.406
|View full text |Cite
|
Sign up to set email alerts
|

Biological and social correlates of blood pressure among Japanese men in Hawaii.

Abstract: SUMMARY A cohort of more than 8000 Japanese men living in Hawaii was studied for factors associated with blood pressure levels, with an emphasis on biological and sociocultural variables. Bivariate and multivariate analyses of more than 50 variables indicated that obesity, age, hematocrit, heart rate, forced vital capacity, serum triglyceride, serum uric acid, cigarette consumption, and family history of hypertension were independently associated with both cross-sectional levels and longitudinal changes in blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
39
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 20 publications
7
39
0
Order By: Relevance
“…On the other hand, some studies have reported that baseline alcohol consumption is significantly associated with baseline blood pressure, but not with changes in blood pressure during the observation period. 13,14 These conflicting findings suggest that the effects of initial daily alcohol consumption on changes in blood pressure remain unconfirmed. Our study found, nevertheless, that initial daily alcohol consumption significantly and independently associates with changes in systolic and diastolic blood pressure in middle-aged Japanese workers.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies have reported that baseline alcohol consumption is significantly associated with baseline blood pressure, but not with changes in blood pressure during the observation period. 13,14 These conflicting findings suggest that the effects of initial daily alcohol consumption on changes in blood pressure remain unconfirmed. Our study found, nevertheless, that initial daily alcohol consumption significantly and independently associates with changes in systolic and diastolic blood pressure in middle-aged Japanese workers.…”
Section: Discussionmentioning
confidence: 99%
“…1 With use of reported dietary intake, conflicting evidence was obtained on the relation of protein intake to blood pressure. An inverse relation was found in Japanese 2,3 and Chinese men, 4 and in men from the US with one or more major risk factors for coronary heart disease. 5,6 A direct relation or absence of significant relation were found in other studies.…”
Section: Introductionmentioning
confidence: 93%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Heart rate and cigarette smoking have also been positively related to incidence of hypertension, 3,[5][6][7][8]12,14,[16][17][18] although cigarette smoking has generally been inversely related to blood pressure (BP) in cross-sectional studies. [19][20][21][22][23][24][25][26][27] Education and social status have been inversely related to BP and hypertension in both cross-sectional and prospective studies. 12,16,23,28,29 Only four prospective studies examined one or more of these variables as possible risk factors for hypertension separately in black subjects 9,12,16 or women.…”
Section: Introductionmentioning
confidence: 99%